(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
In this cross-sectional study from October 2020 to September 2021, pulmonary function was assessed in 40 (24 severe and 16 non-severe) post- COVID-19 patients at three months following hospital discharge by convenient sampling in post-COVID follow-up clinic at Department of Respiratory Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka. Among 40 subjects, 17 (42.5%) had restrictive defect, 1 (2.5%) had obstructive defect and 22 (55%) had normal spirometry. There was reduced total lung capacity (TLC) in 17 (42.5%) subjects and reduced diffusing lung capacity for carbon monoxide (DLCO) in 20 (50%) subjects. Mean six minutes walking distance (6MWD) was low (387.6±99.4 meters). Oxygen desaturation was in 4 (10%) cases. Frequency of restrictive defect was higher in severe than non-severe subjects (54.2% vs. 25%). Reduced TLC was in 62.5% of severe and 12.5% of non-severe cases. There was higher frequency of reduced DLCO in severe than non-severe casese (62.5% vs. 31.3%). 6MWD was lower in severe than non-severe group (354.0±134.9 vs. 438.2±51.4 meters, P=0.02). Pulmonary function was found significantly impaired in post-COVID patients which was more prominent in severe disease group. BSMMU J 2022; 15(3): 192-196